Extending the potential of the dual-mode dual-fuel combustion towards the prospective EURO VII emissions limits using gasoline and OMEx. (1st April 2021) - Macián, Vicente; Monsalve-Serrano, Javier; Villalta, David; Fogué-Robles, Álvaro
Highlights: Complete dual-fuel engine calibration to fulfill tentative EURO VII emissions levels. OMEx-gasoline leads to higher efficiency than diesel-gasoline fuel combination. Homologation and real driving conditions considered for the results analysis. The use of OMEx allows reaching the CO2 2030 target in a well-to-wheel base. Abstract: Dual-mode dual-fuel (DMDF) combustion strategy has been corroborated to be a potential combustion mode to achieve ultra-low NOx and soot emissions, as requested by the future regulations on internal combustion engines. In addition, the synthetic fuels have arisen in the last years for overcoming the problem of total emissions of CO2 over the fuel life cycle. In the case of DMDF, poly-oxymethylene dimethyl ether (OMEx) has been found a promising alternative to diesel when combined to gasoline. In this sense, the OMEx-gasoline combination promotes ultra-low NOx and zero-soot emissions while maintaining the engine performance and acceptable levels of other regulated emissions. The main objective and novelty of this work is to experimentally evaluate the potential of this architecture to reach post-EURO VI NOx emissions levels at engine-out conditions by means of a dedicated engine calibration. Moreover, to evaluate the implications of using synthetic fuels for the European objectives in terms of CO2 impact considering different driving conditions scenarios by means of a virtual vehicle model. The results show that the OMEx-gasoline DMDF engine can reach engine-out NOx emissions below 0.2 g/kWh with zero-soot emissions in all engine operating map and the impact on fuel consumption is lower than 4% with respect to conventional diesel operation. Also, the H2030 target of 30% CO2 reduction can be achieved in a well-to-wheel base.